Shifting the mindset regarding adherence to antibiotic use for respiratory tract infections - Carl Llor (Exploratory Research in Clinical and Social Pharmacy)
Some papers emphasize adherence to antibiotic therapy, but a paradigm shift is needed. While nonadherence may impact chronic conditions, it has not been proven to affect community respiratory tract infections outside of tuberculosis. Respiratory infections, which account for most community antibiotic prescriptions, often involve inappropriate antibiotic use, even in developed countries, with up to 80 % of consultations resulting in prescriptions. Over-the-counter sales of antibiotics further exacerbate this issue. Research should explore whether stopping antibiotics after symptom resolution, rather than completing the full course, is feasible for non-severe infections. Shorter antibiotic courses have shown similar effectiveness with fewer side effects, aligning with the “shorter is better” principle. The idea that completing the entire antibiotic course prevents antimicrobial resistance remains unproven. Instead, longer exposure to antibiotics increases resistance. A patient-centered approach, focusing on outcomes, is essential for the future of antibiotic stewardship.